Implementing p53 Expression in Colorectal Cancers in Ugandan Patients - Richard Wismayer; Julius Kiwanuka; Henry Wabinga; Michael Odida (Medical Research and Its Applications Vol. 10, 2024)
Aim: The aim of the study was to determine the association of p53 expression with grade, stage, LVI status, histopathological subtype and topography of CRC. Introduction: The topography of colon tumours is also different with right-sided colon tumours more commonly observed in developed high-income countries whilst many Sub-Saharan African countries report a high proportion of left-sided colon tumours, especially rectal tumours. In Uganda, the Kampala Cancer Registry has reported a steady increase in colorectal cancer (CRC) in the past 20 years, however, is still lower compared to developed high-income countries. Colon tumour topography varies as well; in industrialized high-income countries, right-sided colon tumours are more frequently detected than in developing low-income ones. In colorectal cancer (CRC), the p53 gene is often altered. This leads to the production of an aberrant protein, which can be detected early by immunohistochemistry. A poor prognosis and reduced survival have been associated with the detection of p53 in malignant cells. Methods: During the period 2008 to 2021, immunohistochemistry was carried out on 51 patients’ paraffin-embedded tissue blocks of CRC. TP53 expression was detected using the indirect immunoperoxidase method which uses monoclonal antibody p53, DAKO Agilent USA, Clone DO-7. The grade and histopathological subtypes of CRC were evaluated using the haematoxylin and eosin stain. The demographic data and topography of the tumours were obtained from the clinical patients’ files and the Kampala Cancer Registry. Results: Out of 51 patient tissue blocks that were studied, 27(52.9%) expressed p53 in the nucleus of malignant CRC cells. There were 20(74.1%) left-sided colon tumours and 7(25.9%) right-sided colon tumours that expressed p53 and this reached statistical significance (p=0.0004). The presence of p53 expression was also significantly associated with the presence of lymphovascular invasion (p=0.0561) and the classical adenocarcinoma histological subtype (p=0.0000). There was a negative correlation between CRC grade and p53 expression (r=-0.1189; p=0.4059) and between CRC stage and p53 expression (r=-0.1702; p=0.2324). The present study did not evaluate the role of radiotherapy in the response to rectal tumours that have positive p53 expression, however, future studies may evaluate this role in Ugandan patients. Similar to other parts of the world in Ugandan patients, p53 expression is more commonly present in left-sided colon tumours. Conclusions: The intensity of p53 expression is not influenced by stage and grade of CRC. Similar to other parts of the world, p53 expression is more commonly present in left-sided tumours. Therefore these findings support the theory, that right-sided colon tumours have a different pathogenesis than left-sided colon tumours, and hence have a different prognosis. Further studies should be carried out to determine the types of genetic mutations or epigenetic factors responsible for the difference in prognosis between left-sided and right-sided CRC in Ugandan patients.